Waste Management Initiatives in India its types and Challenges - Dr. Rajbala Saiwal (Universal Research Reports, 2023)
The purpose of authoring this article is to investigate existing practices connected to various waste management initiatives implemented in India for human well-being. The other goal is to make suggestions and recommendations to improve waste management procedures in Indian towns. This work relies on secondary research. It provides in-depth understanding of India's numerous waste management projects and identifies areas for development in waste management for societal benefit. The purpose of this study is to better comprehend the essential role that the formal sector plays in waste management in our country. This is an original piece that could be expanded upon.